WEBINAR BUDIKDAMBER DI LAHAN TERBATAS SEBAGAI PENYEDIA PANGAN KELUARGA - Yuli Andriani; Rusky Intan Pratama (Universitas Mataram, 2022)
The COVID-19 pandemic has had an impact on the entire community in various sectors. One of the problems faced is the decline in the level of the economy. It reduces the people's purchasing power for fishery commodities. This will reduce the fulfillment of nutritional needs, especially protein. One of the skills that can be learned as an alternative business as well as to meet nutritional needs, especially protein is Budikdamber (Fish Cultivation in Buckets) which can be done on limited land at low cost. The purpose of this community service activity is to disseminate information about the meaning, method of making, and maintaining fish in buckets (budikdamber). This service is carried out through several stages, namely the preparation stage, the counseling implementation stage, and the evaluation stage. During the webinar preparation stage, the activities carried out include the division of tasks, discussions on the concept of the event, publication of webinar flyers, and rehearsals. The implementation stage is carried out by holding a webinar